Prognosis of Non-small-cell Lung Cancer Patients With Lipid Metabolism Pathway Alternations to Immunotherapy - Cheng, Tianli; Zhang, Jing; Liu, Danni; Lai, Guorong; Wen, Xiaoping (Frontiers in Genetics, 2021)
Immune checkpoint inhibitors (ICIs) significantly improve the survival of patients with non-small-cell lung cancer (NSCLC), but only some patients obtain clinical benefits. Predictive biomarkers for ICIs can accurately identify people who will benefit from immunotherapy. Lipid metabolism signaling plays a key role in the tumor microenvironment (TME) and immunotherapy. Hence, we tried to explore the association between the mutation status of the lipid metabolism pathway and the prognosis of patients with NSCLC treated with ICIs. We downloaded the mutation data and clinical data of a cohort of patients with NSCLC who received ICIs. Univariate and multivariate Cox regression models were used to analyze the association between the mutation status of the lipid metabolism pathway and the prognosis of patients treated with ICIs. Additionally, The Cancer Genome Atlas (TCGA)-NSCLC cohort was used to explore the relationships between the different mutation statuses of lipid metabolism pathways and the TME. In the immunotherapy cohort, high numbers of mutations in the lipid metabolism pathway could be used as an independent predictor of better prognosis in patients with NSCLC treated with ICIs (HR = 0.683; P = 0.0190). Additionally, we found that patients with high numbers of mutations in the lipid metabolism pathway had significantly enriched M0 macrophages, M1 macrophages, activated memory CD4+ T cells, CD8+ cells, follicular helper T cells and gamma delta T cells, significantly increased expression of inflammatory genes (interferon-γ (IFNG), CD8A, GZMA, GZMB, CXCL9 and CXCL10) and enhanced immunogenic factors (neoantigen loads, tumor mutation burden and DNA damage repair pathways). A high number of mutations in the lipid metabolism pathway is associated with significantly prolonged progression-free survival (PFS) in NSCLC, indicating that a high number of mutations in the lipid metabolism pathway can be used as a predictive marker for patients with NSCLC receiving ICIs.